he effects of functional microbial agents on the soil microbial communities of high-frigid grassland under desertification in Northwest Sichuan - Xia Yuan; Cuiyu Li; Yi Tang; Zhiyu Chen; Chunping Huang (Botanica Serbica, 2022)
Grassland desertification seriously destroys the structure of the soil microbial communities and further accelerates the deterioration of grassland. In this study, functional microbial agents were sprayed on degraded grasslands and studied by means of real-time fluorescence quantitative PCR and high-throughput sequencing methods. The aim was to investigate the effects of microbial agents on the soil microbial community structure and soil remediation functions in different degraded grasslands (LDG: light desertification grassland, MDG: medium desertification grassland, and HDG: heavy desertification grassland). The results showed that after treatment with the microbial agents, bacterial abundance increased by 96.24% (LDG), 95.19% (MDG), and 93.47% (HDG), respectively, and fungal abundance increased by 85.77% (LDG), 95.85% (MDG) and 22.49% (HDG), respectively. Further, with the colonisation and acclimatisation of foreign functional microorganisms, the microbial agents greatly influenced the structure of the soil microbial community, increased the microbial diversity index, and significantly changed the microbial community composition. The application of the microbial agents did not only improve the forage yield and quality, but also guided the soil restoration, improved the soil water content of sandy grassland, adjusted the soil pH, significantly increased the content of soil organic matter, total nitrogen, and total phosphorus, and also inhibited the growth of soil-borne pathogens. Our findings provide new ideas and guidance for the management of degraded grassland